Negative allosteric modulation of GluN1/GluN3 NMDA receptors. (1st October 2020) - Zhu, Zongjian; Yi, Feng; Epplin, Matthew P.; Liu, Ding; Summer, Samantha L.; Mizu, Ruth; Shaulsky, Gil; XiangWei, Wenshu; Tang, Weiting; Burger, Pieter B.; Menaldino, David S.; Myers, Scott J.; et al.
Abstract: NMDA receptors are ligand-gated ion channels that mediate excitatory neurotransmission. Most native NMDA receptors are tetrameric assemblies of two glycine-binding GluN1 and two glutamate-binding GluN2 subunits. Co-assembly of the glycine-binding GluN1 with glycine-binding GluN3 subunits (GluN3A-B) creates glycine activated receptors that possess strikingly different functional and pharmacological properties compared to GluN1/GluN2 NMDA receptors. The role of GluN1/GluN3 receptors in neuronal function remains unknown, in part due to lack of pharmacological tools with which to explore their physiological roles. We have identified the negative allosteric modulator EU1180-438, which is selective for GluN1/GluN3 receptors over GluN1/GluN2 NMDA receptors, AMPA, and kainate receptors. EU1180-438 is also inactive at GABA, glycine, and P2X receptors, but displays inhibition of some nicotinic acetylcholine receptors. Furthermore, we demonstrate that EU1180-438 produces robust inhibition of glycine-activated current responses mediated by native GluN1/GluN3A receptors in hippocampal CA1 pyramidal neurons. EU1180-438 is a non-competitive antagonist with activity that is independent of membrane potential (i.e. voltage-independent), glycine concentration, and extracellular pH. Non-stationary fluctuation analysis of neuronal current responses provided an estimated weighted mean unitary conductance of 6.1 pS for GluN1/GluN3A channels, and showed that EU1180-438 has no effect on conductance. Site-directed mutagenesis suggests that structural determinants of EU1180-438 activity reside near a short pre-M1 helix that lies parallel to the plane of the membrane below the agonist binding domain. These findings demonstrate that structural differences between GluN3 and other glutamate receptor subunits can be exploited to generate subunit-selective ligands with utility in exploring the roles GluN3 in neuronal function. Highlights: EU1180-438 is negative allosteric modulator selective for GluN1/GluN3 receptors. EU1180-438 inhibits current responses mediated by neuronal GluN1/GluN3A receptors. EU1180-438 activity is independent of membrane potential and agonist concentration. Structural determinants of EU1180-438 activity reside near the GluN3A pre-M1 helix. EU1180-438 is a tool to investigate the physiology of native GluN1/GluN3 receptors.